Pengaruh Pemberian Ekstrak Daun Mengkudu (Morinda Citrifolia) terhadap Histologi Ginjal Tikus Jantan - Ratna Dewi; Noviyanti Noviyanti (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Oxidative stress induced by cigarette smoke exposure can cause damage to various organs, including the kidneys and liver. Noni leaves (Morinda citrifolia) are known to possess high antioxidant activity that may protect against such damage. This study aimed to evaluate the histopathological changes in the liver and kidneys of male rats exposed to cigarette smoke and treated with methanol extract of noni leaves. A true experimental design was employed using 40 male rats randomly divided into five groups: a negative control group and four treatment groups exposed to cigarette smoke with varying doses of noni leaf extract (0, 100, 200, and 300 mg/kg body weight) administered for 52 days. Kidney and liver tissues were collected, processed histologically, and stained with hematoxylin-eosin for microscopic examination. The results showed that cigarette smoke exposure caused renal damage characterized by glomerular injury, tubular necrosis, and hemorrhage. However, administration of noni leaf extract, particularly at doses of 200 and 300 mg/kg, demonstrated protective effects by reducing the severity of renal histological damage. These findings suggest that noni leaf extract has a dose-dependent renoprotective potential against oxidative stress induced by cigarette smoke, possibly attributed to its antioxidant, anti-inflammatory, and free radical-scavenging activities. Further research is recommended to explore its hepatoprotective effects and underlying molecular mechanisms.